Personal Branding Puteri Indonesia 2024 di Media Sosial Instagram - Dimas Bagus Laksono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Instagram is one of the social media that plays an important role in shaping the self-image of public figures in the digital era. Puteri Indonesia as a representation of Indonesian women is not only required to appear aesthetically pleasing, but also to build a strong and authentic personal branding through digital media. This study aims to examine the personal branding strategy of Puteri Indonesia 2024, Harashta Haifa Zahra, through her official Instagram account. The research approach uses a descriptive qualitative method with a constructivism paradigm through case studies. Data collection techniques include digital observation, upload documentation, and in-depth interviews with key informants. The results of the study show that personal branding is built through the representation of leadership values, social concern, and authenticity that are conveyed consistently. The use of Instagram's interactive features such as Live, Q&A, and Stories strengthens two-way communication with the audience. These findings indicate that social media not only functions as a tool for forming an image, but also as an effective relational medium in establishing emotional closeness with the public.